Spin-Orbit-Coupling-Governed Optical Absorption in Bilayer MoS2 via Strain, Twist, and Electric Field Engineering - Lianmeng Yu; Yingliang Chen; Weibin Zhang; Peizhi Yang; Xiaobo Feng (Nanomaterials)
This paper investigates strain-, twist-, and electric-field-tuned optical absorption in bilayer MoS2, emphasizing spin-orbit coupling (SOC). A continuum model reveals competing mechanisms: geometric perturbations (strain/twist) and Stark effects govern one-/two-photon absorption, with critical thresholds (~9% strain, ~2.13° twist) switching spin-independent to spin-polarized regimes. Strain gradients and twist enhance nonlinear responses through symmetry-breaking effects while electric fields dynamically modulate absorption via band alignment tuning. By linking parameter configurations to absorption characteristics, this work provides a framework for designing tunable spin-resolved optoelectronic devices and advancing light–matter control in 2D materials.